Prognosis of patients with laryngeal contact granuloma: Development and validation of RCGSG score - Yufei Pan; Jinrang Li; Xiaoyu Wang; Jinhong Zhang; Chun Zhang; Zhi Liu (Laryngoscope Investigative Otolaryngology)
Abstract Objective This study aimed to develop an objective and simple score for predicting the prognosis of patients with laryngeal contact granuloma (LCG) treated with local glucocorticoid injection combined with oral proton pump inhibitor (GI + PPI). Methods Cox regression analysis was used to analyze the effect of baseline variables on the prognosis of 507 patients with LCG treated with GI + PPI. An easy‐to‐apply RCGSG (Reflus, Cough, Gender, and Surgery in GI + PPI therapy) score was developed based on the independent risk factors selected by univariate and multivariate Cox regression analyses. The score was internally validated by receiver‐operating characteristic curve, calibration curve, and decision curve analysis. Results After univariate and multivariate analyses, male gender (hazard ratio [HR] 0.546, p < .001), laryngopharyngeal reflux (HR 0.702, p = .001), chronic cough (HR 0.709, p = .001), and history of surgical resection (HR 0.433, p < .001) were found to be the independent risk factors affecting the prognosis of LCG. According to the score, the median cure time was 3 months (95% confidence interval [CI] 2.81–3.19) in the low‐risk group, 4 months (95% CI 3.74–4.26) in the moderate‐risk group, and 5 months (95% CI 4.76–5.24) in the high‐risk group. The bootstrap method was used to plot calibration curves for internal validation. Conclusion The RCGSG score, developed based on laryngopharyngeal reflux, chronic cough, gender, and surgical resection history, has been internally verified to be a good predictor of the prognosis of patients with LCG receiving GI + PPI treatment. Level of evidence Level 4.